THE GENESIS OF ENGINEERING KNOWLEDGE IN THE VIEWS OF EASTERN THINKERS IN THE MIDDLE AGES (Eureka Journal of Humanities and Social Research, 2025)
This article examines the renaissance in engineering and exact sciences in the medieval Eastern world. Using the example of Al-Khwarizmi, Ibn Sina, Al-Basari, Beruni, and Alkhazen, we can study how engineering knowledge based on experimental natural science developed in the East. We can consider that inventions and engineering achievements brought to Europe by the East, such as mechanical clocks, compasses, gunpowder, paper, played a huge role in the development of European civilization.
Keywords: Optics